PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE EVERYONE IS A TEACHER HERE DISERTAI HANDOUT TERHADAP HASIL BELAJAR BIOLOGI KELAS XI DI SMAN I TALAMAU PASAMAN BARAT - Yanti, Sustra Indri (Pendidikan Biologi, 2014)
The basic of this research by the result of biology learning in second grade students at SMAN I Talamau west Pasaman is low. This caused by some factors, that is the students do not active in learning and less sources of book at school. The purpose of this research is to know the effect of application the active learning strategy type everyone is a teacher here by using handout toward the result of biology learning in second grade student at SMAN I Talamau west Pasama. This research uses experiment method with randomized control group only design. The result of this research from affective, kognitif, psikomotor that exist to the students percentase experiment class that complete 90,48% and in class control 88%. The result of data analysis showed that t arithmetic 3,04 > t table 1,67 with the hyphotesis was accepted. It means that the aktive laerning strategy type everyone is a teacher here by using handout can improve the result of biology learning and second grade students at SMAN I Talamau west Pasaman.